Baculovirus Utilizes Cholesterol Transporter NIEMANN–Pick C1 for Host Cell Entry - Li, Zhihong; Fan, Youpeng; Wei, Junhong; Mei, Xionge; He, Qiang; Zhang, Yonghua; Li, Tian; Long, Mengxian; Chen, Jie; Bao, Jialing; Pan, Guoqing; Li, Chunfeng; et al. (Frontiers in Microbiology, 2019)
The dual roles of baculovirus for the control of natural insect populations as an insecticide, and as a tool for foreign gene expression and delivery, have called for a comprehensive understanding of the molecular mechanisms governing viral infection. Here, we demonstrate that the Bombyx mori Niemann-Pick C1 (BmNPC1) is essential for baculovirus infection in insect cells. Both pretreatment of Bombyx mori embryonic cells (BmE) with NPC1 antagonists (imipramine or U18666A) and down-regulation of NPC1 expression resulted in a significant reduction in baculovirus BmNPV (Bombyx mori nuclear polyhedrosis virus) infectivity. Disruption of BmNPC1 could decrease viral entry (2 hpi) rather than reduce the viral binding to the BmE cells. Furthermore, our results showed that NPC1 domain C binds directly and speciﬁcally to the viral glycoprotein GP64, which is responsible for both receptor binding and fusion. Antibody blocking assay also revealed that the domain C specific polyclonal antibody inhibited BmNPV infection, indicating that NPC1 domain C most likely plays a role during viral fusion in endosomal compartments. Our results, combined with previous studies identifying an essential role of human NPC1 (hNPC1) in filovirus infection, suggest that the glycoprotein of several enveloped viruses possess a shared strategy of exploiting host NPC1 proteins during virus intracellular entry events.